The importance of comprehensive support based on the three pillars of exercise, nutrition, and sleep for improving core symptoms of autism spectrum disorders - Yano, Nozomu; Hosokawa, Kenji (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is classified as a neurodevelopmental disorder. The Diagnostic and Statistical Manual of Mental Disorders (DSM)-V, which first described ASD, lists persistent deficits in social communication and interrelationships, as well as limited and recurrent modes of behavior, interests, and activities as diagnostic items. Until recently, understanding the pathophysiology of ASD has been mostly from a neurophysiological perspective, and interventions have been mostly behavioral and psychological. In recent years, however, it has become clear that ASD also affects many bodily systems, including the immune system, the sensorimotor system, and the gut-brain axis, and that these factors simultaneously influence it. In light of this background, a new “connectivome theory” has been proposed as a hypothesis for understanding ASD. “Exercise,” “nutrition,” and “sleep,” which are discussed in this mini-review, have a particularly strong relationship with the immune, musculoskeletal, and gut systems among the pathologies mentioned in the “connectivome theory,” furthermore, many reports suggest improvements in stereo-responsive behavior and social and communication skills, which are the core symptoms of ASD. In addition, these interventions are characterized by being less subject to location and cost limitations and excel in the continuity of therapeutic intervention, and the three interventions may have a reciprocal positive impact and may function as three pillars to support ASD.